Risk factors influencing the occurrence of anthrax outbreaks at the Livestock-Game interface in Katunguru, Rubirizi district, Uganda - Nannozi BK; Kebirungi P; Asiimwe; Mweheire I; Ademun AR; Mugaya H; Ndyamgayo G; Ndyanabo S; Ayebazibwe C; Nizeyimana G; Okuthe S; Magona JW (International Journal of Veterinary Science and Research - Peertechz Publications, 2022)
Anthrax outbreaks are very frequent and recurrent in the Rubirizi district in landing sites along the Kazinga channel in the Queen Elizabeth National Park in Uganda. This has persistently caused huge losses of domestic and wild animals and increased public health risks to communities. A participatory disease search (PDS) was thus conducted to identify risk factors that influence the recurrent occurrence of the outbreaks. Using PDS tools, including, Focus group discussion, Mapping, Seasonal calendars, Timelines and Pairwise ranking, local communities were engaged to recall detailed information regarding previous anthrax outbreaks. The number of persons that participated in focus group discussions ranged from 16 in Kazinga landing site to 22 in Katunguru, 18 in Kashaka landing site and 20 in Kishenyi landing site The findings revealed anthrax outbreaks had been reported previously in Katunguru, Kyabakara, Katera, Kingu and Ryeyu sub-counties  of Rubirizi district that lie within or adjacent to the Queen Elizabeth National Park. The last anthrax outbreak occurred in 2014. Death of goats and sheep and wild animals, especially, hippopotami was reported in the landing sites of Kazinga, Katunguru, Kishenyi and Kashaka in Katunguru Subcounty. Uganda Wildlife Authority (UWA) established burial sites for carcasses of dead hippopotami in Kazinga and Kishenyi landing sites.  Key risk factors associated with anthrax outbreaks (see attached ranks) in Rubirizi district included: (1) Frequent droughts and associated floods (2.5); (2) Dwelling in landing sites normally used as burial areas for carcasses of dead animals by Uganda Wildlife Authority (2.8); (3) Free movement of goats and sheep and intermingling with wildlife at landing sites along Kazinga channel (3.0); (4) Community habit of eating the meat of dead wild or domestic animals (3.8); (5) Communities eating not well-cooked meat (4.0); (6) Ignorance among communities regarding anthrax and its mode of spread (4.8); (7) Frequent migration of communities from landing sites with low to those with a high risk of anthrax disease (6.5); (8) Grazing domestic animals in close proximity with wildlife in the Game Park (6.8); (9) Communities consuming game meat (8.0); and (10) Frequent occurrence of anthrax outbreaks and spread of anthrax spores through floods and existing water bodies (8.3).  In conclusion, the PDS case study successfully identified risk factors associated with anthrax outbreaks in Katunguru Subcounty of Rubirizi district in Uganda. Sensitization of communities on anthrax, its mode of spread and effective and sustainable control was recommended in order to contain anthrax outbreaks.